The role of the Hygiene Department of Stephen Bathory University in the development and promotion of Public Health in Vilnius in the years 1922–1939 - Aistis Žalnora (Studia Historiae Scientiarum)
Objective: During the interwar period, the healthcare system in Europe experienced a dramatic transformation. It was perceived that preventive medicine was no less important than curative medicine. Moreover, without proper prevention of the so-called social diseases, all later therapeutic measures were expensive and ineffective. The former battle against the consequences was replaced by measures targeting the causes. The fight against social diseases involved a state-owned strategy and a broad arsenal of measures. The University’s scholars also took part in this process. Our study revealed that the significance of the disease prevention in the Faculty of Medicine at the University of Stephen Bathory was well understood. Moreover, the treatment was not segregated from hygiene as strictly as it is today. Many hygienists as well as clinicians contributed to the development of preventive mechanisms. The broad specialization of doctors enabled them to see not only biomedical, but also social and economic aspects of a disease. Hygienists and doctors encouraged cooperation and coordination of their activities with the central and local authorities as well as education of the local population.